The Concept of Real Right in India and South Africa: Specifics of National Regulation and Trends of Harmonization of Law - FROLOVA, Evgenia; BELIKOVA, Ksenia; BADAEVA, Natalia; BELOZEROVA, Irina; ULIANISCHEV, Victor (Journal of Advanced Research in Law and Economics, 2017)
The prospects and ways of improving the real right legislation are examined on the example of two legal systems of the BRICS countries – India and South Africa. General and special features of legal regulation in the considered area are defined. India’s legislation was studied using the main act in the field – the Transfer of Property Act of 1882, as well as a number of other acts regulating proprietary relationships. The law of South Africa was explored using doctrinal sources, statutory and case law. The article presents conclusions on the ways and directions for bridging the gap in the legislation of these two countries in the regulation of property rights. The authors point out that acknowledging the need for legal approximation and striving to achieve the goals set, the governments will understand that only a flexible approach and gradual adoption of legal institutions used in other legal systems, their adaptation, as well as measures aimed at overcoming the conservatism in established procedures can ensure successful harmonization of law. At the same time, unification of the civil law will become a significant accompanying factor in enhancing cooperation between the two states.